Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.)Di Pre Nursery Terhadap Pemberian Limbah Lumpur Kering Crude Palm Oil (CPO) - Rostian Nafery; Miranty Trinawaty; Desailly Wahyuna (Jurnal Agroekoteknologi, 2022)
This study aims to examine the influence of dry mud waste oil palm on the growth oil palm (Elaeis gueneensis Jacq.) fledgling in pre nursery. This research has been conducted at Semambu Island, Indralaya District, Ogan Ilir Regency, South Sumatra Province. This research was conducted from August 2020 until October 2020.The method used in this study is an experimental method, using a Randomized Group Design.  The treatments oil palm dry sludge waste with five level and five replications. The treatments in this study were P0 = 0%, P1 = 20%, P2 = 40%, P3 = 60%, P4 = 80%. The observed variables were plant height, leaf area, stem diameter and root volume.The application of dry sludge from crude palm oil factory has a good effect on the growth of plant height, leaf area, stem diameter, and root volume with a dose of 40% oil palm dry sludge waste obtained the best plant height 19,61 cm, leaf area is 88,51 cm2, stem diameter 7,53 mm and root volume is 5,80 ml.